Efficacy indicators for ICT addiction prevention: a case study of Clickeando - Amparo Luján Barrera; Lydia Cervera Ortiz; Mariano Chóliz Montañes (Revista Española de Pedagogía)
There are few programmes for preventing ICT addiction, and even fewer that have been scientifically validated. Preventing ICT addiction is a key part of governments’ adolescent mental health policies. Clickeando is a school programme for universal prevention of ICT addiction in adolescents. It has been in use for fourteen years and was designed on the basis of the appropriate quality indexes for this type of programme. Since 2020, Clickeando has assessed its participants with the aim of linking the efforts of different preventive bodies and agents. This has enabled the present study to assess the programme’s impact on its target population. The main results indicate that the programme produces changes in ICT use, principally by reducing addictive use of mobile phones by girls and boys in secondary education. Likewise, there are important behaviours in the development of addictive patterns that we suggest should be the focus of future modifications to the workshop (such as time spent on social networks or on instant messaging systems), for they are crucial for the efficacy of the intervention. The effects of Covid-19 on young people’s mental health have highlighted the need for assessment protocols and preventive actions that foster healthy use of technology and that take into account age and the gender perspective in their implementation to maximise their efficacy.